Utilizing digital technology for education on minor illness treatment for the community at Rusun Mawar Penjaringan - Lusy Noviani; Ledianasari Ledianasari; Clarissa Max; Lily Agista Nurfazriah; Florensia Irena Angellika; Meirisa Meirisa; Michael Kim Putra Jaya; Patrick Renata; Valeska Aurelia Sulisyanto; Vandy Vandy; Deka Prismawan (Universitas Muhammadiyah Magelang, 2024)
The lack of public knowledge regarding online medicine purchases for minor ailments is the main concern of this program. According to BPOM data in 2021, online medicine purchases increased by 480% during the Covid-19 pandemic, reflecting the growing public need for online access to medications. However, this surge comes with the risk of purchasing errors that could jeopardize health. To address this issue, a digital education program was conducted at Rusun Mawar Penjaringan to enhance public knowledge and awareness about safe and correct online medicine purchases. The program utilized interactive lectures and questionnaires. Participants underwent a pre-test to measure their initial understanding of online medicine purchases, followed by a post-test after the education session to evaluate knowledge improvement. Results showed a significant increase, with 70.5% of participants correctly answering post-test questions compared to their pre-test results. This program not only contributes to improving public digital health literacy but also serves as a preliminary step toward fostering awareness of safe and appropriate online medicine purchasing practices.